Nasopalatine duct cyst occurring after secondary alveolar bone grafting: A case report. Issue 2 (14th December 2021) - Kobayashi, Yoshikazu; Kyo, Iyo; Satoh, Koji; Isomura, Madoka; Urano, Makoto
Abstract: Background: We describe an exceedingly rare case of a nasopalatine duct cyst that developed after bone grafting into an alveolar cleft. Case presentation: A 10‐year‐old male patient with a unilateral lip and alveolar cleft underwent alveolar bone grafting. Computed tomography at the 1‐year follow‐up revealed a well‐defined, round radiolucency including the grafted bone and the incisive canal. Cystectomy and bone grafting were performed, and the resected specimen was histopathologically diagnosed as a nasopalatine duct cyst. The postoperative course was good and bone bridging was achieved, including at the alveolar cleft. Conclusion: Based on our observations and the findings of previous reports, surgical stimulation due to alveolar bone grafting was suggested to have caused the NDC.